IMPROVING STUDENT CREATIVITY AND LEARNING OUTCOMES THROUGH THE PODCAST-BASED INQUIRY LEARNING MODEL - Anny Wahyuni; Puji Sumanggar; Ekawarna Ekawarna; Jonathan C Gano-an (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2022)
This study aimed to increase creativity and student learning outcomes through a podcast-based inquiry learning model. This research was conducted at SMA PGRI 2 Jambi City in February-April 2022, with the subjects of this research being students of class X IPS 2. This type of research was classroom action research which was conducted six times. The data were obtained using questionnaires, observations, interviews, documentation studies, and field notes which were then analyzed through qualitative descriptive techniques. The results showed that the application of the podcast-based inquiry learning model to history subjects had gone well. The test results showed that the average value of learning outcomes had increased from 70.5 in cycle I to 83.3 in cycle VI. The average student creativity scores also increased from cycle I, with a score of 70.5 to 84.2 in cycle VI. These numbers show that the podcast-based inquiry learning model can improve student learning outcomes and creativity.